Pelatihan Sistem Informasi Manajemen Data pada Sumber Daya Manusia Kesejaterahan Sosial - Wiharto, Yudi; Subandi Subandi; Mufti, Mufti; Gata, Grace; Aryasanti, Agnes (Institut Teknologi dan Bisnis Semarang, 2024)
This activity discusses the importance of training in implementing data management information systems to increase the efficiency and effectiveness of human resource (HR) management in the context of social welfare. Data management information systems provide a structured framework for managing HR data, enabling organizations to make better and faster decisions. However, the successful implementation of this system depends on HR's understanding and skills regarding its use. Therefore, this activity proposes a comprehensive training program for HR that focuses on the use of data management information systems. Effective training methods include practical learning, case simulations, and interactive sessions to ensure in-depth understanding and practical application of the material studied. Through this approach, it is hoped that organizations can improve the performance of their human resources in managing social welfare data, which will ultimately have a positive impact on operational efficiency and effectiveness as well as the resulting social impact.